Pengaruh pupuk kandang kambing dan pupuk daun terhadap pertumbuhan tanaman selada merah (Lactuca Sativa L) - Nurhayati, Dewi Ratna; Noviyanti, Risti Wahyu; Bahri, Saiful (Jurnal Agrotek Ummat, 2022)
Red lettuce (Lactuca sativa L) is a seasonal plant and belongs to the Asteracea family, this plant is often used as a staple food that contains various vitamins and minerals. The research was carried out from November 2021 to January 2022 in the experimental garden of the Faculty of Agriculture, Slamet Riyadi University, Surakarta. The purpose of this study was to determine the response of red lettuce to goat manure and fertilizer. Completely randomized design (CRD) with 2 treatments used in this study, first using goat manure as follows: Goat manure content of 0 gr/polybag, Goat manure with a content of 150 grams/polybag and Goat manure with a content of 300 gr/tan . While the second treatment used foliar fertilizers with 3 factors, namely foliar fertilizers with a concentration of 0%, foliar fertilizers with a concentration of 9 ml/polybag and foliar fertilizers with a concentration of 18 ml/polybags. Based on the results of this study, red lettuce plants had the best response to goat manure 300 g/polybag and leaf fertilizer concentration of 18 ml/polybag at plant height 75.60 cm, number of leaves 61.14 strands, leaf length 73.05 cm, dry weight of stover 45.29 grams and dry root weight 37.63 grams.